Assessment of Availability of Traditionally used Flora in Curing Jaundice in Central Himalayan Region - Tewari2, Priti Kumari1,2, G. C. Joshi1*, L. M. (Journal of Phytology, 2011)
Plants are used extensively for treatment of different ailments. However, the introduction of allopathic drugs decreased human dependency on medicinal plants. In the present world where industrialization accompanied with urbanization has greatly modified the values and life standards of the majority of population. The folk knowledge of people pertinent to medicinal plants uses are in danger of being lost forever. It was thus considered worthwhile to document the folk uses of medicinal plants for curing important human diseases. The manuscript provides traditional uses of plant species in curing jaundice by the local community residing in Almora district of Central Himalaya. The study examined the community structure of documented species. Vegetation analysis of species was analysed and identifying three forest area along an altitude of 500-1200m, 1200-2000m and 2000-2800m. 12 species were documented in this study of which herb (7), shrub (3), and climber (2). In majority of cases, extract from the whole plant were used for curing jaundice, followed by root, fruit. After statistical analysis, community was identified as heterogeneous. It is said that interest in medicinal plants is increasing as an alternative to modern medicine, so there is an urgent need for conservation of this valuable treasure. It is urgent to spreading awareness of conservation among common people and young generation must be made obligatory. It is necessary that sustainable harvesting techniques should be adopted so as to protect the species in the wild. It forms an important criterion that these medicinal plants should be used in a sustainable way in order to preserve for future generation.